POTENSI NUTRISI DAN SENSORI PERMEN JELLY DARI SEMANGKA AFKIR - Putri, Zikra Askia; Anggraini, Ezi; Faridah, Anni; Mustika, Sari (Ensiklopedia Research and Community Service Review, 2025)
Abstract: The global food crisis and the high level of food waste, especially in horticultural commodities which reach 30-50%, encourage the urgency of innovation in the use of agricultural products that have been neglected so far. This study aims to analyze the effect of afkir watermelon puree substitution on the quality of jelly candy, as an effort to increase the added value of local commodities. The study used a purely experimental design with four afkir watermelon puree substitution treatments (0%, 25%, 50%, and 75%) and three repetitions. The test included sensory analysis (rating test) and hedonic test with 30 semi-trained panelists. The results of the rating test showed a significant increase in all parameters along with the increase in the percentage of substitutions. In color parameters, the value increased from 1.19 (X0) to 5.46 (X3), the aroma expanded from 2.64 (X0) to 5.99 (X3), the texture remained chewy with a range of 4.57-5.37, and the complex taste increased from 4.79 (X0) to 5.71 (X3).  The hedonic test confirmed the findings, with favorability scores increasing consistently; color from 3.99 (X0) to 5.64 (X3), chewy texture from 4.06 (X0) to 5.14 (X3), aroma from 4.38 (X0) to 5.50 (X3), and taste from 4.83 (X0) to 5.44 (X3). The X3 treatment (75% substitution) consistently showed the highest sensory characteristics and receptivity rates. This research proves the potential of afkir watermelon as a raw material for quality jelly candy, with a significant product transformation: the color develops from neutral white to red-orange, the aroma of watermelon is getting more intense, the texture remains chewy, and the sweetness is getting more complex. These findings open up new perspectives in the utilization of local food resources and food waste reduction strategies.Keywords: Watermelon Afkir, Jelly Candy, Sensory Test, Hedonic Test.